2003
DOI: 10.1086/378818
|View full text |Cite
|
Sign up to set email alerts
|

Microduplication 22q11.2, an Emerging Syndrome: Clinical, Cytogenetic, and Molecular Analysis of Thirteen Patients

Abstract: Chromosome 22, particularly band 22q11.2, is predisposed to rearrangements due to misalignments of low-copy repeats (LCRs). DiGeorge/velocardiofacial syndrome (DG/VCFS) is a common disorder resulting from microdeletion within the same band. Although both deletion and duplication are expected to occur in equal proportions as reciprocal events caused by LCR-mediated rearrangements, very few microduplications have been identified. We have identified 13 cases of microduplication 22q11.2, primarily by interphase fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
319
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(342 citation statements)
references
References 28 publications
14
319
2
5
Order By: Relevance
“…The phenotype of both syndromes is variable, with shared clinical anomalies that include heart defects, urogenital abnormalities, and velopharyngeal insufficiency. [27][28][29] The incidence of the DiGeorge syndrome is estimated to be 1 case in 4000 births. 30 The 22q11.2 microduplication syndrome appears to be less prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of both syndromes is variable, with shared clinical anomalies that include heart defects, urogenital abnormalities, and velopharyngeal insufficiency. [27][28][29] The incidence of the DiGeorge syndrome is estimated to be 1 case in 4000 births. 30 The 22q11.2 microduplication syndrome appears to be less prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the clinical presentations due to microduplications of a given genomic segment can be significantly different from those seen in the corresponding microdeletion syndrome. [10][11][12][13][14][15] Furthermore, microduplications that are responsible for clinical phenotypes may be inherited from apparently unaffected carrier parents. [25][26][27] Repnikova et al 28 have reported a patient with a 600-kb duplication in chromosome 2q23.1 that included MBD5 and EPC2.…”
Section: Discussionmentioning
confidence: 99%
“…A well-known example is the duplication of chromosome region 17p12 that causes CharcotMarie-Tooth disease type 1A syndrome and the corresponding deletion that causes hereditary neuropathy with liability to pressure palsies. 9 Other examples include duplications reciprocal to the recurrent deletions associated with Willams-Beuren syndrome, 10 velo-cardio-facial syndrome, 11 Smith-Magenis syndrome, 12 neurofibromatosis I, 13 Sotos syndrome, 14 and Rett syndrome. 15 Duplications of chromosome region 2q23.1 have not been described to date and the clinical consequences are currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…Such deletions are a known cause of human disease; identifying the reciprocal duplications and documenting their role in generating specific phenotypes is one of the challenges of modern human genetics. Duplications reciprocal to the recurrent deletions associated with velo-cardio-facial syndrome, 4 the Williams-Beuren syndrome 5 and the Smith-Magenis syndrome 6 have been documented. In addition, newly described phenotypes associated with deletions and duplications in regions of the genome previously not known to be causative of human disease [7][8][9][10][11][12] have arisen.…”
Section: Introductionmentioning
confidence: 99%